2019
DOI: 10.1021/acs.orglett.9b02501
|View full text |Cite
|
Sign up to set email alerts
|

Rh(III)-Catalyzed Coupling of N-Chloroimines with α-Diazo-α-phosphonoacetates for the Synthesis of 2H-Isoindoles

Abstract: We report herein the first use of N-chloroimines as effective synthons for directed C–H functionalization. Rh­(III)-catalyzed coupling of N-chloroimines with α-diazo-α-phosphono­acetates allows for efficient dechlorinative/dephosphonative access to 2H-isoindoles. Further deesterification under Ni­(II) catalysis enables the complete elimination of reactivity-assisting groups and full exposure of reactivity of C3 and N2 ring atoms for attaching structurally distinct appendages.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 37 publications
0
8
0
Order By: Relevance
“…They have pointed out that indole (analogue of A-1 ) is stable while isoindole and indolizine (analogues of A-2 and A-4 , respectively) are unstable on the basis of several calculations on aromaticity, as corroborated by the fact that isoindole was synthesized 80 years later than indole . In these respects, A- m molecules except for A-1 are predicted not to be synthesized easily, but recent developments for the synthetic root of sp 2 -hybritized aza compounds including isoindole , are expected to pave a way for the synthesis of the promising A- m molecules.…”
Section: Results and Discussionmentioning
confidence: 99%
“…They have pointed out that indole (analogue of A-1 ) is stable while isoindole and indolizine (analogues of A-2 and A-4 , respectively) are unstable on the basis of several calculations on aromaticity, as corroborated by the fact that isoindole was synthesized 80 years later than indole . In these respects, A- m molecules except for A-1 are predicted not to be synthesized easily, but recent developments for the synthetic root of sp 2 -hybritized aza compounds including isoindole , are expected to pave a way for the synthesis of the promising A- m molecules.…”
Section: Results and Discussionmentioning
confidence: 99%
“…Because of high coordinating and oxidizing reactivity N ‐chloroimine synthon will find wide applications in transition‐metal‐catalyzed C–H functionalization. [ 34 ] Herein, we presented some metal‐catalyzed, metal‐free, and photocatalytic C–H chlorination reactions with N–Cl compounds serve this purpose.…”
Section: Oxidative Transformations (C–cl and C–o)mentioning
confidence: 99%
“…Zhu et al [ 34 ] reported the utility of N ‐chloroimines as effective substrates for C–H functionalization for the synthesis of 2H‐isoindoles (Scheme 63) Herein 2H‐isoindoles are synthesized by the coupling of N ‐chloroimines with α‐diazo‐α‐phosphonoacetates in the presence of Rh(III) catalyst, and the reaction proceeds via de‐esterification. The structural variation with the exposure of C3 and N2 ring atoms is illustrated by the ability to achieve electrophilic substitution and nucleophilic reaction, respectively.…”
Section: Application Of N‐cloroimines For the Racemization Of 1‐phenylethylamine And Preparation Of Isoquinolines And 2‐h Isoindolesmentioning
confidence: 99%
“…In 2019, Qi et al reported a Rh(III)-catalyzed coupling of N-chloroimines 76 with -diazo--phosphonoacetates 77 that provided dechlorinative/dephosphonative access to 2H-isoindoles 78 (Scheme 18). 66 This was the first reported use of N-chloroimines for directed C-H functionalization. To generate a cationic Rh(III) catalyst, AgBF 4 was used as a halide-abstraction reagent.…”
Section: Rhodium-catalyzed Synthesismentioning
confidence: 99%